Volatilidade no mercado de ações brasileiro e seu impacto sobre as regras de política monetária: 2003 2009 - Besarria, Cassio da Nobrega (2010)
This dissertation has as objective to estimate the relationship between monetary policy and the volatility of asset prices using the model BEKK, from January 2003 to October 2009. The specific objectives were: a) model the volatility of the Bovespa Index (Bovespa) and the Selic, referring to the money and stock through GARCH models, b) verify the clustering of volatility, the presence of persistent shocks and perform the analysis half-life in the financial market variables, c) estimate Vector Autoregressive models with the aim of testing the causal relationships in the sense of Granger (Granger Causality) between the transmission mechanism of monetary policy (interest rates) and the index stock; To achieve these objectives we used the model proposed by Bernanke, Gertler (1999, 2000) to describe the effects of volatility in monetary policy rules, and to capture the effects of volatility in monetary policy decisions were used in models family univariate and multivariate GARCH. The test of Granger causality show that there is unidirectional causality Ibovespa Selic regarding the period of greater volatility in the stock market (2003 - 2008), indicating that the returns in the stock market affected the Brazilian monetary policy decisions in this period . The estimation of GARCH models TARCHI and noted the existence of agglomeration of the variance, the effect of leverage on volatility and persistence on the part of stock markets and money. Through the model BEKKER is possible to highlight the volatility of the Selic rate is positively affected by common shocks and their lags inflation volatility, the volatility of the Bovespa index had a direct relationship with the volatility of the Selic rate in the period (2003 - 2008). This fact is consistent with the effects of movements in asset prices on aggregate demand, thus suggesting that policymakers are responding to changes in the market to avoid possible negative impacts on the economy.